TRANSPORT DEVELOPMENT IN CHINA AND CENTRAL ASIA IN THE CONTEXT FORMATION OF TRANS-EURASIAN TRANSPORT CORRIDORS - E. V. Savkovic; A. G. Dankov (Сравнительная политика, 2015)
Abstract: In accordance with its economic interests, China advances coherent policy for development of transport infrastructure both on its own territory and in neighbouring countries. Throughout the last two decades it facilitated the widening trade activity and broader economic cooperation between Xinjiang Uygur Autonomous Region and Central Asian states. Its further development foresees a network of Trans-Eurasian links, which will connect China not only with all nearby countries, but with European region as well.